Bir Yoğunlaştırılmış Güneş Enerjisi Santrali İçin Organik Rankıne Çevrimi Dizaynı Ve Modellemesi - Acar, Erdem (Enerji Enstitüsü, 2017)
Güneş enerjisini kullanılabilir bir enerji formuna dönüştüren farklı türde pek çok pasif veya aktif güneş enerjisi dönüştürme sistemi vardır. Aktif güneş enerjisi dönüştürme sistemlerindeki en önemli unsur olan güneş kolektörleri (termal veya fotovoltaik), üzerlerine gelen güneş ışınımını yakalar ve onu kullanılabilir bir enerji formuna (ısı ya da elektrik) dönüştürürler. Güneş termal kolektörler yüzeylerine düşen güneş ışınımını, tiplerine ve yüzey özelliklerine göre belli oranda emerek ya da yansıtarak ısıya dönüştürürler ve bu ısıyı, kolektör boyunca uzanan boru veya borular içinden akan bir ısı transfer akışkanına transfer ederler. Güneş enerjisinden dönüştürülen kullanılabilir enerjinin özellikle termal enerjinin sıcaklık seviyesini yükseltmek, ısı kayıpları olan kolektör yüzeyini küçülterek kolektörün verimini arttırmak, daha ucuz ve kullanışlı bir kolektör oluşturmak için yoğunlaştırıcı güneş termal kolektörler kullanılır. Yoğunlaştırılmış güneş enerjisi santralleri, çeşitli tip yansıtıcı yüzey ve alıcıdan oluşan kolektör düzenekleri kullanarak güneş enerjisini yüksek sıcaklıklarda ısıya dönüştürür ve bu ısıdan geleneksel bir buhar türbini ve jeneratör aracılığıyla elektrik üretir. Yoğunlaştırılmış güneş enerjisi santralleri temelde iki ana kısımdan oluşur. Bunlar: güneş enerjisinin toplandığı ve ısıya dönüştürüldüğü güneş kolektör alanı (varsa termal enerji depolama sistemini de içerir) ve ısı enerjisinin bir termodinamik güç çevrimi ile elektriğe dönüştürüldüğü güç bloğudur. Yoğunlaştırılmış güneş enerjisi santrallerinde kullanılan yoğunlaştırıcı güneş termal kolektörler, yalnızca yüzeylerine gelen direkt güneş ışınımını yakalar ve onu yansıtarak bir alıcıda yoğunlaştırır. Üzerinde yoğunlaştırılan güneş ışınımını emerek ısınan alıcı, bu ısıyı içindeki ısı transfer akışkanına transfer eder. Varsa termal enerji depolama sisteminden geçen ısı transfer akışkanı, borular aracılığıyla taşınarak güç bloğundaki ısı değiştiricisine ulaşır ve ısısını güç çevriminde kullanılan çalışma akışkanına transfer eder. Isınarak buhar fazına geçen çalışma akışkanı da türbin-jeneratör sistemini çalıştırır ve böylece elektrik üretilir. Yoğunlaştırılmış güneş enerjisi santrallerinde en çok tercih edilen tür teknoloji ise bugün mevcut güneş termal enerji teknolojileri içinde en olgun ve en düşük maliyetli teknoloji olan, parabolik oluk kolektör teknolojisidir. Parabolik oluk kolektörlerin kullanıldığı yoğunlaştırılmış güneş enerjisi santrallerinde, güneş kolektör alanının boyutuna ve yerleşim planına bağlı olarak belli boyutta ve sayıda parabolik oluk kolektör düzenekleri kullanılır. Bu tez çalışmasında, düşük sıcaklıklarda çalışan ve sınırlı bir çıkış gücü (< 1 MWe) olan yenilenebilir enerji kaynaklı güç santrallerinde kullanıldığında ekonomik bir şekilde elektrik üretilmesini sağlayan Organik Rankine Çevrimi (ORÇ)'nin, İzmir'de kurulacağı varsayılan bir parabolik oluk kolektörlü yoğunlaştırılmış güneş enerjisi santrali için dizaynı ve modellemesi yapılmıştır. Bu amaçla "System Advisor Model (SAM)" adlı program kullanılarak güneş kolektör alanı dizaynı, "Flownex" adlı simülasyon programı kullanılarak da güç bloğu dizaynı ve modellemesi yapılmıştır. Referans olarak, ABD'nin Arizona eyaletinde yer alan, ORÇ ile çalışan bir güç bloğunun kullanıldığı ve 1 MW net elektrik üretim kapasitesine sahip olan "Saguaro" adlı parabolik oluk kolektörlü yoğunlaştırılmış güneş enerjisi santrali kullanılmıştır. Yenilenebilir enerji güç sistemleri projeleri için yapılan modellemelerde sistem dizayn parametrelerini kullanarak, kurulum ve işletim maliyetlerini de göz önünde bulundurarak, saatlik sistem performansı ve enerji maliyeti tahminleri yapan SAM programıyla; kolektör düzenekleri tarafından emilen, güneş kolektör alanından çıkan ve güç bloğuna aktarılan saatlik, aylık ve yıllık tahmini toplam termal enerji miktarları hesaplanmıştır. Güç bloğundaki ORÇ'nde kullanılmak üzere; termodinamik, çevre, emniyet ve proses ile ilgili olan değerlendirme kriterleri göz önünde bulundurularak, çalışma akışkanı olarak R245fa (pentafloropropan) seçilmiştir. Bir düşük sıcaklık çalışma akışkanı olan ve ağırlıklı olarak atık ısı geri kazanımı uygulamalarında kullanılan R245fa, ABD Çevre Koruma Ajansı (EPA) onaylı ve Montreal Protokolü kapsamında kullanımına izin verilen hidroflorokarbon (HFC) soğutucuları ailesinin bir üyesidir. Birçok çeşit termal ve akışkan sistemin kararlı ve dinamik durumları için dizayn, analiz ve optimizasyon yapılmasını sağlayan Flownex simülasyon programıyla da güç bloğunun, kararlı durum ve dinamik durum için ORÇ modellemesi yapılmıştır. Oluşturulan türbin ve pompa performans eğrileri kullanılarak kararlı durum için yapılan ORÇ modellemesinde, güç bloğu için çalışma sıcaklığı aralığı belirlenmiş ve güç bloğunda üretilecek tahmini yıllık brüt elektrik miktarı hesaplanmıştır. Kararlı durumda çalışan güç bloğunun bileşenlerinde oluşacak herhangi bir değişim durumunda; türbinde üretilen brüt güç, sıcaklık, basınç, kütlesel debi gibi parametrelerde meydana gelecek değişimleri önceden görebilmek amacıyla oluşturulacak senaryolar için, 9 Temmuz günü saat 07.00-17.00 arasındaki zaman dilimi seçilmiş ve bir dinamik durum modellemesi yapılmıştır.

There are many different types of passive and active solar energy conversion systems that convert solar energy into a useful form of energy. Solar energy is captured and converted by solar thermal collectors into heat which is then supplied to a demand for thermal energy such as domestic heating, hot water heating, or heat for industrial processes. If the demand to be met is electricity rather than heat, there are two common methods of converting solar energy into electricity. One method is by collecting solar energy as heat and converting it into electricity using a typical power plant or engine; the other method is by using photovoltaic cells to convert solar energy directly into electricity. Solar thermal collectors are special kinds of heat exchangers that transform solar radiation energy to internal energy of the transport medium. The solar thermal collector is the key element in an active solar energy conversion system. This is a device that absorbs the incoming solar radiation, converts it into heat, and transfers the heat to a fluid (usually air, water, or oil) flowing through the collector. Flat plate solar thermal collectors are the most commonly used type of solar collector. Their construction and operation are simple. A large plate of blackened material is oriented in such a manner that the solar energy that falls on the plate is absorbed and converted to thermal energy thereby heating the plate. Tubes or ducting are provided to remove heat from the plate, transferring it to a liquid or gas, and carrying it away to the thermal energy. One or more transparent (glass or plastic) plates are often placed in front of the absorber plate to reduce heat loss to the atmosphere. Likewise, opaque insulation is placed around the backside of the absorber plate for the same purpose. Operating temperatures up to 125 °C are typical. When higher temperatures are required, concentrating solar thermal collectors are used. Solar energy falling on a large reflective surface is reflected onto a smaller area before it is converted into heat. This is done so that the surface absorbing the concentrated energy is smaller than the surface capturing the energy and therefore can attain higher temperatures before heat loss due to radiation and convection wastes the energy that has been collected. Most concentrating solar thermal collectors can only concentrate the parallel insolation coming directly from the sun's disk (direct normal insolation), and must track the sun's path across the sky. Parabolic trough collector technology has been proven to be the most mature and lowest cost solar thermal energy technology to generate heat for solar thermal electricity generation or process heat applications available today. As a result, most of the projects for the construction of commercial solar thermal power plants are based on this type of collectors and several parabolic trough solar thermal power plants are going to be constructed in USA, Spain, Northern Africa, Middle East, etc. Parabolic trough collectors can effectively produce heat at temperatures between 60 °C and 400 °C. Parabolic trough collectors are made by bending a sheet of reflective material into a parabolic shape. A black metal tube, covered with a glass tube to reduce heat losses, is placed along the focal line of the receiver. A parabolic trough collector concentrates incoming solar radiation onto a line running the length of the trough. A receiver tube carrying heat transfer fluid is placed along this line, absorbing concentrated solar radiation and heating the fluid inside, thus transforming the solar radiation into useful heat. It is sufficient to use a single axis tracking of the sun; therefore, long collector modules are produced. Because the surface area of the receiver tube is small compared to the trough aperture area, temperatures up to 400 °C can be reached without major heat loss. Concentrating solar thermal power plants produce electricity by converting the sun's energy into high temperature heat using various mirror configurations. The heat is then channeled through a conventional generator. The plants basically consist of two main parts: solar collector area that collects solar energy and converts it to heat, and power block that converts heat energy to electricity. Concentrating solar thermal power systems can be sized 10 kW or grid connected applications up to 100 MW. Some systems use thermal storage during cloudy periods or at night. Concentrating solar thermal power plant technologies is based on four basic elements: concentrator, receiver, transport-storage, and turbine-generator. The collector captures and concentrates solar radiation, which is then delivered to the receiver. The receiver absorbs the concentrated sunlight, transferring its heat energy to a working fluid which would be synthetic oil. The transport-storage system passes the fluid from the receiver to the turbine-generator. In this thesis, APS (Arizona's serving electricity utility) Saguaro Power Plant facility located in Arizona, USA was used as a reference solar thermal power plant. The Saguaro Power Plant was initially have 10340 square meters of parabolic trough solar field supplied by Solargenix and it was be nominally a 1 MWe generating capacity Organic Rankine Cycle (ORC) system with wet cooling supplied by Ormat. The Saguaro Power Plant was designed for possible expansion of the solar field and addition of thermal storage at some point in the future. The Rankine cycle is the most commonly used cycle in conventional power plants. The ORC is generally used in heat recovery applications at low temperature. ORC technology is similar to the steam cycles technology; a working fluid is pumped to a tank where it is evaporated, and it is heated to vaporization by solar thermal energy. The steam is then expanded in a turbine to produce mechanical energy and then electricity through a generator. This steam is then condensed to close the thermodynamic cycle. The difference between a conventional cycle and an organic cycle is that the working fluid in organic cycle is an organic fluid. The working fluids that are most appropriate in ORC units are dry fluids, which must have a relatively low temperature and critical pressure. General criteria taken into consideration to identify the most suitable organic fluids include thermodynamic properties, stability of the fluid, compatibility with materials in contact with the fluid, safety and environmental aspects, availability, and costs. After analysis related to security, availability and environmental compatibility (ODP and GWP), working fluids are considered; R245fa (pentafluoropropane) was selected as a working fluid in ORC for this thesis. In this thesis, System Advisor Model (SAM) program was used for the solar collector area design. SAM is a performance and financial model for renewable energy power systems and projects. SAM makes performance predictions and cost of energy estimates for grid connected power projects based on installation and operating costs and system design parameters that are specified as inputs to the model. SAM is developed by the National Renewable Energy Laboratory (NREL) in collaboration with Sandia National Laboratories, and the University of Wisconsin, at first used internally by the US Department of Energy's Solar Energy Technologies Program for systems based analysis of solar technology improvement opportunities within the program. SAM's performance model makes hour by hour calculations of a power system's electric output, generating a set of 8760 hourly values that represent the system's electricity production over a single year. In this thesis, Flownex simulation program was used for the power block design and modeling. Flownex provides a complete thermal-fluid design and analysis solution; it is developed by M-Tech Industrial, South Africa. Flownex combines a very extensive range of simulation (include both steady state and dynamic simulations) capabilities to provide the most complete solution for system and sub‐system level simulations currently available. Flownex is an integrated systems CFD code used for the design, simulation and optimization of complete thermal-fluid systems. The analysis of thermal-fluid networks is based on the numerical solution of the governing equations of fluid dynamics and heat transfer. Flownex solves the partial differential equations for mass, momentum and energy conservation to obtain the mass flow rate, pressure and temperature distributions throughout a network.
Design And Modeling Of Organic Rankine Cycle For A Concentrated Solar Thermal Power Plant
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Enerji Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Energy Institute, 2014
Keywords: Enerji; Güneş enerjisi; Energy; Solar energy; Solar heating